2021
DOI: 10.3390/polym13162807
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Modification of Chitosan via Reactive Solvent-Free Extrusion

Abstract: Hydrophobic derivatives of polysaccharides possess an amphiphilic behavior and are widely used as rheological modifiers, selective sorbents, and stabilizers for compositions intended for various applications. In this work, we studied the mechanochemical reactions of chitosan alkylation when interacting with docosylglycidyl and hexadecylglycidyl ethers in the absence of solvents at shear deformation in a pilot twin-screw extruder. The chemical structure and physical properties of the obtained derivatives were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In contrast, chitin nanocrystals are heat stable up to 250–300 °C [ 62 , 63 ] and, therefore, are better candidates for the production of active packages. When comparing chitosan with chitin nanoparticles, chitin has better miscibility than hydrophobic polylactic acid (chitosan is more hydrophilic) [ 64 , 65 ], which has been linked to improved mechanical and barrier properties [ 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, chitin nanocrystals are heat stable up to 250–300 °C [ 62 , 63 ] and, therefore, are better candidates for the production of active packages. When comparing chitosan with chitin nanoparticles, chitin has better miscibility than hydrophobic polylactic acid (chitosan is more hydrophilic) [ 64 , 65 ], which has been linked to improved mechanical and barrier properties [ 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobization is usually carried out by introducing alkyl substituents of various lengths into the structure of CS due to reactions of its amino groups with fatty acids or their anhydrides (acylated derivatives) or by interaction with aldehydes followed by the reduction of azomethine bonds to secondary amines (alkylated derivatives) [ 133 ]. These hydrophobically modified CSs can create self-assembled nanoparticles to encase hydrophobic drugs in their core [ 134 , 135 ].…”
Section: Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…The band at 1070 cm −1 is attributed to C-O stretching vibrations of the CHOH, and CH 2 OH groups in the ring. [64][65][66][67] Attachment of silver nanoparticles to the CH modified film surfaces caused the significant decrease in intensity of OH and NH 2 stretching band region, which indicates the chelation of silver with both amino and hydroxyl groups of chitosan. The shift of the characteristic C=O, N-H, and C-O bands of chitosan to 1664, 1598, and 1080 cm −1 , respectively, and the decrease in their intensity suggested that it is an effect of the existence of interactions between Ag and O, N atoms of OH and NH 2 groups.…”
Section: Surface Properties Of Modified Filmsmentioning
confidence: 99%